PENGARUH EFISIENSI PASAR SAHAM TERHADAP KEPUTUSAN TRANSAKSI SAHAM: PENDEKATAN CAPITAL ASSET PRICING MODEL - Asadyawan Putra; Agus Suman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research journal explains the effect of stock market efficiency as an observation in investors' decisions to carry out IPO transactions for PT issuers. GOTO Gojek Tokopedia LockUp and Post LockUp period. The research begins in April 2022 to August 2023, using the concept of the Capital Asset Pricing Models approach which consists of calculating Company Beta (β), Risk Free Rate, and Risk Premium. The data used is in panel form with secondary characteristics originating from PT IPO price data. GOTO, historical stock prices, historical IHSG data, and BI-7DRR. This journal obtained two results, first, stock return (Ri) had a significant positive effect on expected return in the LockUp period, but stock return (Ri) had a significant negative effect on expected return in the Post LockUp period. It can be concluded that investors have greater return expectations during the LockUp period. Second, the Post LockUp period reversed to the LockUp period, where stock returns had a positive value, while expected returns had a negative value.